Longitudinal Impact of Sleep Duration on Liver Stiffness Velocity in Metabolic Dysfunction-Associated Steatotic Liver Disease: A Five-Year Prospective Cohort Study (Journal of Rangpur Medical College, 2026)
Background: The clinical shift from non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated steatotic liver disease (MASLD) emphasizes identifying modifiable drivers of fibrotic progression. While obesity and diabetes are established risk factors, the independent impact of sleep duration on the "velocity" of liver stiffness measurement (LSM)-the longitudinal rate of change-remains poorly characterized. Objective: This study aimed to quantify the 5-year relationship between sleep duration and liver stiffness velocity. Methods: We conducted a prospective cohort study of 1,076 participants in Bangladesh (Dhaka, Rangpur, Sylhet) from 2020 to 2025. Baseline and 5-year liver stiffness were measured using vibration-controlled transient elastography (VCTE). Sleep duration was assessed via the Pittsburgh Sleep Quality Index (PSQI). Multivariable regression and causal mediation analysis evaluated the impact of sleep on LSM change (Δ LSM). Results: Over 5 years, 19.7% of individuals were Progressors. Multivariable regression established sleep duration as a potent independent predictor of liver stiffness velocity (β=-0.20,95% CI: -0.28, -0.12, p